An Integrated Approach to Fragment-Based Lead Generation:Philosophy, Strategy and Case Studies from AstraZeneca's Drug Discovery Programmes - Albert, Jeffrey S.; Blomberg, Niklas; Breeze, Alexander L.; Brown, Alastair J. H.; Burrows, Jeremy N.; Edwards, Philip D.; Folmer, Rutger H. A.; Geschwindner, Stefan; Griffen, Ed J.; Kenny, Peter W.; Nowak, Thorsten; Olsson, Lise-Lotte; et al. (Current Topics in Medicinal Chemistry, 2007)
Fragment-based lead generation (FBLG) has recently emerged as an alternative to traditional high throughput screening (HTS) to identify initial chemistry starting points for drug discovery programs. In comparison to HTS screening libraries, the screening sets for FBLG tend to contain orders of magnitude fewer compounds, and the compounds themselves are less structurally complex and have lower molecular weight. This report summarises the advent of FBLG within the industry and then describes the FBLG experience at AstraZeneca. We discuss (1) optimising the design of screening libraries, (2) hit detection methodologies, (3) evaluation of hit quality and use of ligand efficiency calculations, and (4) approaches to evolve fragment-based, low complexity hits towards drug-like leads. Furthermore, we exemplify our use of FBLG with case studies in the following drug discovery areas: antibacterial enzyme targets, GPCRs (melanocortin 4 receptor modulators), prostaglandin D2 synthase inhibitors, phosphatase inhibitors (protein tyrosine phosphotase 1B), and protease inhibitors (b-secretase).
Keywords: ligand efficiency